2001
DOI: 10.1097/00000433-200106000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Position Paper on Fatal Abusive Head Injuries in Infants and Young Children

Abstract: This article represents the work of the National Association of Medical Examiners Ad Hoc Committee on shaken baby syndrome. Abusive head injuries include injuries caused by shaking as well as impact to the head, either by directly striking the head or by causing the head to strike another object or surface. Because of anatomic and developmental differences in the brain and skull of the young child, the mechanisms and types of injuries that affect the head differ from those that affect the older child or adult.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
8

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(79 citation statements)
references
References 51 publications
0
70
0
8
Order By: Relevance
“…Using DTI as a biomarker for axonal injury could markedly improve the efficiency of such trials. In a forensic investigation, the approximate age of a pericontusional traumatic white matter lesion could be assessed to either confirm or call into question the reports of witnesses or other evidence (Case et al, 2001;Oehmichen et al, 2003). A growing body of forensic imaging literature supports this possibility (Kahana and Hiss, 1999;Thali et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Using DTI as a biomarker for axonal injury could markedly improve the efficiency of such trials. In a forensic investigation, the approximate age of a pericontusional traumatic white matter lesion could be assessed to either confirm or call into question the reports of witnesses or other evidence (Case et al, 2001;Oehmichen et al, 2003). A growing body of forensic imaging literature supports this possibility (Kahana and Hiss, 1999;Thali et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that SDH is commonly observed in sTBI secondary to AHT, [27][28][29] and therefore children suffering from AHT comprised a natural population for study. Herein, we found that neurologic exam and most radiographic hallmarks do not seem to predict HH.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of blood, typically 2-15 ml, into the subdural space is not of itself harmful. 7 It provides firm evidence of shaking in the absence of a history of severe accidental head trauma.…”
Section: Pathophysiologymentioning
confidence: 97%